2020
DOI: 10.1001/jamaoto.2019.4788
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-Centered Functional Outcomes Questionnaire in Head and Neck Cancer

Abstract: Incorporation of patient perspectives, or patient-reported outcomes, in functional outcome measures has been gaining prominence in the literature on reconstructive surgery. OBJECTIVE To create and validate an instrument for measuring the main functional areas of concern for patients with head and neck cancer. DESIGN, SETTING, AND PARTICIPANTS This 4-phase mixed-methods qualitative study was conducted from July 1, 2013, to June 30, 2016, in a quaternary head and neck oncology center in Edmonton, Alberta, Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…48 These PROMs are often developed from patient populations where the majority have undergone surgery involving the aerodigestive tract. 31 For example, the Edmonton-33 instrument, a commonly used PROM in head and neck cancer patients, was designed and tested only in patients with squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, and larynx, 49 whereas OncoQuest, a PROM measuring HRQL in head and neck cancer patients, was validated in a patient population where 78% of patients had tumors of the pharynx, larynx, or oral cavity. 50 The PROM developed in this study is the first to specifically address outcomes related to the midface.…”
Section: Discussionmentioning
confidence: 99%
“…48 These PROMs are often developed from patient populations where the majority have undergone surgery involving the aerodigestive tract. 31 For example, the Edmonton-33 instrument, a commonly used PROM in head and neck cancer patients, was designed and tested only in patients with squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, and larynx, 49 whereas OncoQuest, a PROM measuring HRQL in head and neck cancer patients, was validated in a patient population where 78% of patients had tumors of the pharynx, larynx, or oral cavity. 50 The PROM developed in this study is the first to specifically address outcomes related to the midface.…”
Section: Discussionmentioning
confidence: 99%
“…In examining treatment outcomes and priorities, previous studies used measures developed by investigators [ 24 , 25 ]. It is now well-recognized in clinical practice and research that patients’ perspectives are essential from the outset to fully understand their care experience and assess treatment options [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In examining treatment outcomes and priorities, previous studies used measures developed by investigators [ 24 , 25 ]. It is now well-recognized in clinical practice and research that patients’ perspectives are essential from the outset to fully understand their care experience and assess treatment options [ 24 , 25 ]. In our study, we wanted to explore if there are valuable priorities that are missed by investigators and which can only be identified by individuals who experienced HNC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey among head and neck surgeons, more than half reported that they do not systematically record functional outcomes, in part because the instruments are too cumbersome and the time required is too long. In contrast to other common otorhinolaryngologic diseases such as chronic rhinosinusitis [ 25 , 26 ], simple, clinically applicable instruments for recording HNC-related basic physical and mental functions are rare [ 8 , 27 ]. The aim of this study was to develop and validate an instrument to assess a basic functional status of HNC patients at oncological follow-up visits.…”
Section: Discussionmentioning
confidence: 99%